Preliminary study to determine the potential use of extracts of Prosopisflexuosa (algarrobo) and Rutachalepensis (ruda) in drugs formulation (Veterinary Science, 2017)
The effect of the oral administration of hydroalcoholic extracts of Prosopisflexuosa and Prosopisalpataco was evaluated on thegastric motility in a canine. This preliminary study was conducted in order to determine if these extracts, the same as in mice, delay gastric emptying. The aim of these tests is to evaluate new compounds that can be formulated with antiparasitic drugs as albendazole, to promote absorption by increasing the time they spend in contact with stomach acid pH The results of these tests determined that Prosopisflexuosa do not produce variations in the gastric emptying time, increasing intestinal motility. The dose of Rutachalepensis hydroalcoholic extract used in these assays was toxic producing increased gastric motility and vomits. We conclude that further studies should be performed using lower doses to determine the potential of these extracts
Keywords: Albendazole; Prosopis flexuosa; Ruta chalepensis